Cell division and endoreduplication play important roles in stem swelling of tuber mustard (Brassica juncea Coss. var. tumida Tsen et Lee) - Shi, H.; Wang, L. L.; Sun, L.T.; Dong, L. L.; Liu, B.; Chen, L. P. (Plant biology (Stuttgart, Germany), 2012)
We investigated spatio‐temporal variations in cell division and the occurrence of endoreduplication in cells of tuber mustard stems during development. Cells in the stem had 8C nuclei (C represents DNA content of a two haploid genome), since it is an allotetraploid species derived from diploid Brassica rapa (AA) and B. nigra (BB), thus indicating the occurrence of endoreduplication. Additionally, we observed a dynamic change of cell ploidy in different regions of the swollen stems, with a decrease in 4C proportion in P4‐1 and a sharp increase in 8C cells that became the dominant cell type (86.33% at most) in the inner pith cells. Furthermore, cDNAs of 14 cell cycle genes and four cell expansion genes were cloned and their spatial transcripts analysed in order to understand their roles in stem development. The expression of most cell cycle genes peaked in regions of the outer pith (P2 or P3), some genes regulating S/G2 and G2/M (BjCDKB1;2, BjCYCB1;1 and BjCYCB1;2) significantly decrease in P5 and P6, while G1/S regulators (BjE2Fa, BjE2Fb and BjE2Fc) showed a relative high expression level in the inner pith (P5) where cells were undergoing endoreduplication. Coincidentally, BjXTH1and BjXTH2 were exclusively expressed in the endoreduplicated cells. Our results suggest that cells of outer pith regions (P2 and P3) mainly divide for cell proliferation, while cells of the inner pith expand through endoreduplication. Endoreduplication could trigger expression of BjXTH1 and BjXTH2 and thus function in cell expansion of the pith tissue.